The reciprocal cross effect between local and commercial chickens on growth performance and estimating some genetic parameters - Mohammed Sulaiman Abdullah (Kufa Journal for Agricultural Sciences)
This study was carried out in private field  Kani Graw  – Erbil city during the periods from  1/8/2021 to 20/11/2021 by using two genotypes of chickens, Kurdish local chickens (KK) and Super Harco commercial dual-purpose chickens (HH) which were reciprocally mated to produce four combinations ( HH , KK ,HK and KH) . body weight among genotypes, general combining ability (GCA) and specific combing ability (SCA), heterotic effect percent (H%), and direct additive effect (DAE) for body weight in two genotypes and their crosses were investigated regarding the  bodyweight at aching, 4, 8 and 12 weeks . GCA and SCA were also used to estimate breeding value (BV) and genetic value (GVFM) for two parents and their crosses.Bodyweight (BW) was measured and analyzed at 4, 8, and 12 weeks of age using full diallel analysis. The results indicated that there were significant differences (P< 0.01) among genetic groups in body weight (BW) at all stages of age. The K ×H genotype recorded the highest value in body weight at age 12 weeks. , general combining ability effects indicated that additive genetic variance was important in determining BW and revealed the superiority of the HH genotype in these traits. This genotype, therefore, may be used as one of the parents if its improvement is sought through crossbreeding. Specific combining ability was significant for BW at all ages, except at hatching, Heterosis estimates showed that crossing between Kurdish males and Super Harco females at all stages of age gave the highest heterotic effects for BW. On the other hand, both cross and reciprocal were positive values for BW at 4 and 8 weeks of age. The HH genotype had the highest value of direct additive effect (DAE) at 12 weeks of age. Both the HH and KK genotypes had negative DAE values at hatching and the HH genotype had positive breeding values for BW ,while the KK genotype had a negative value. The cross had an intermediate breeding value of body weight at the same age .In addition, the genetic value of K×H had the highest value in body weight at 8 and 12 weeks of age.